Portret młodego pisarza oraz nawiązania do twórczości Antona Czechowa w Dzikiej gruszy Nuriego Bilge Ceylana - Domalewski, Adam (Przestrzenie Teorii, 2019)
Domalewski Adam, Portret młodego pisarza oraz nawiązania do twórczości Antona Czechowa w Dzikiej gruszy Nuriego Bilge Ceylana [Portrait of a Young Writer and References to European Literature in Nuri Bilge Ceylan’s The Wild Pear Tree]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 343–355. ISSN 1644-6763. DOI 10.14746/pt.2019.32.18. The article focuses on topics related to literature, especially to the works of Anton Chekhov, in the latest film by Nuri Bilge Ceylan The Wild Pear Tree. Its main character, Sinan, is a young writer, while the film is set in the province of Çanakkale, where ancient Troy was located. The analysis of the picture shows that the director refers to the historicity of the myth of the Trojan War with distrust. Instead, Ceylan portrays a local community immersed in intellectual stagnation and creates his hero as an extremely unlikeable misanthropist, to whom literature cannot bring fulfillment. The character of his father, Idris, introduces another ancient motif to the film – the figure of Sisyphus. The relationship between father and son, which deepens in the finale, brings an unexpected note of optimism to the picture, which in its dramaturgy resembles Anton Chekhov’s literary worlds.